Nitrogen Nutrition and Planting Density Effects on Sunflower Growth and Yield: A Review - Ali, Amjed; Ahmad, Ashfaq; Khaliq, Tasneem; Ali, Anser; Ahmad, Muhammad (Pakistan Journal of Nutrition, 2013)
Sunflower because of its quantity and quality of edible oil occupies an important position in the world among the new oil seed crops. To improve achene yield and quality of sunflower in our country different strategies have been adopted. One is to increase number of plants per unit area, which ultimately needs more nitrogen for its physiological and nutritional requirements. Normally, by increasing plant density decreases plant height, head diameter and 1000-achene weight. On the other hand, generally high rate of nitrogen application leads to more rapid leaf area development, prolongs life of foliage, increases leaf area duration after flowering and enhance on the whole crop assimilation, consequently contributing to increase in seed production. By the N application head diameter, 1000-seed weight, biological yield, seed yield per head, seed yield per plant were increased though harvest index and seed oil concentration were decreased. With the increase of nitrogen supply leaf gas exchange and shoot dry weight parameters improved but beyond that these decreased and optimum nitrogen concentrations were different among cultivars. Seed viability, seedling vigor and cool germination test performance, leaf area index, biomass production, seed weight and seed yield per unit area all were found to increase significantly due to the addition of the high N rate. Grain yield and photosynthesis active radiation absorption increase with increasing nitrogen levels and plant density. However, excess rates of nitrogen by enhancing vegetative growth of aerial parts, prolongs the periods to flowering and physiological maturity. High concentration of nitrogen did not affect specific leaf weight but resulted in more dry matter production per plant. With increase in N supply, RUE might also increase but in a lower order than LAI and IPAR. Nitrogen application appreciably enhanced interception of PAR and RUE of sunflower crop sown in irrigated areas. It is, therefore, concluded that while considering the optimum plant density in sunflower nitrogen should rates should also revised to harvest maximum achene and oil yield.